2008
DOI: 10.1159/000137645
|View full text |Cite
|
Sign up to set email alerts
|

Haemostatic Radiofrequency Ablation Assisted Partial Nephrectomy: Is Radiofrequency Energy a Viable Solution?

Abstract: Aim: We present our experience with partial nephrectomy using radiofrequency energy in patients with kidney cancer. Methods: From July 2002 to February 2007, 15 radiofrequency ablation assisted partial nephrectomies were performed. Five patients had one kidney only. The average tumour size was 34 (range 22–55) mm, and the mean age was 56 (range 45–69) years. The renal pedicle was not clamped. A monopolar cool-tip radiofrequency device under intra-operative ultrasound guidance was used. Our procedure involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Sommer et al [25] reported their experience of CT-guided percutaneous RFA on 22 patients, although with a high mean age (74.2 ± 8.6 years), and half of those patients showed impaired renal function before RFA; their oncologic and functional results were relatively encouraging. The high technical success rate and limited complications demonstrated that percutaneous RFA is an efficient therapy for either initial or recurrent kidney tumors, especially for those elderly patients with comorbidities [26,27]. But when dealing with tumors in proximity to critical structures such as ureter, bowel and renal vessels, a laparoscopic approach may be preferred for its intrinsic possibility to mobilize these structures and for the higher precision and accuracy during tumor targeting [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sommer et al [25] reported their experience of CT-guided percutaneous RFA on 22 patients, although with a high mean age (74.2 ± 8.6 years), and half of those patients showed impaired renal function before RFA; their oncologic and functional results were relatively encouraging. The high technical success rate and limited complications demonstrated that percutaneous RFA is an efficient therapy for either initial or recurrent kidney tumors, especially for those elderly patients with comorbidities [26,27]. But when dealing with tumors in proximity to critical structures such as ureter, bowel and renal vessels, a laparoscopic approach may be preferred for its intrinsic possibility to mobilize these structures and for the higher precision and accuracy during tumor targeting [28].…”
Section: Discussionmentioning
confidence: 99%
“…In our own series we observed urine leak in three patients who underwent RF-assisted partial nephrectomy. RF energy was used to perform partial nephrectomy without clamping renal pedicle [22]. Fortunately, in most cases urine leak resolves spontaneously, sometimes it requires endoscopic management.…”
Section: Cost-effectiveness and Complicationsmentioning
confidence: 99%